If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(1 + -2a) + -3 = -3 + a (1 * -2 + -2a * -2) + -3 = -3 + a (-2 + 4a) + -3 = -3 + a Reorder the terms: -2 + -3 + 4a = -3 + a Combine like terms: -2 + -3 = -5 -5 + 4a = -3 + a Solving -5 + 4a = -3 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. -5 + 4a + -1a = -3 + a + -1a Combine like terms: 4a + -1a = 3a -5 + 3a = -3 + a + -1a Combine like terms: a + -1a = 0 -5 + 3a = -3 + 0 -5 + 3a = -3 Add '5' to each side of the equation. -5 + 5 + 3a = -3 + 5 Combine like terms: -5 + 5 = 0 0 + 3a = -3 + 5 3a = -3 + 5 Combine like terms: -3 + 5 = 2 3a = 2 Divide each side by '3'. a = 0.6666666667 Simplifying a = 0.6666666667
| 2x-111=9 | | (6x^2)-10x=0 | | A=11(x+8) | | 7z+8=-20 | | 2x(2x+2)=4x-4 | | -23x+168=76 | | x(x-3)-x(x+4)=15x-23 | | -8g+2.6=-49.4 | | 7+8x=55 | | 20cos^3(4x)-40sin^2(4x)cos(4x)=0 | | 2x-1=y^2+3 | | 3x+120=15 | | 2(7x+18)= | | -12n+13n= | | 11+11+8+x+8+x= | | 11x+59=-29 | | -78+2x=10x+154 | | -8g+2.6=49.4 | | 8/9-b | | 7-6x=7x+7 | | 7(x-13)=12+5(3x-4) | | 2/3m=-12 | | -2y-6=14 | | 115=5x-390 | | 4(y-3x)=y-5x | | y-5+3y=31 | | 5m+4-7=10 | | 2x/(x^2-1)=5/x | | (4m^-2n^8)^1/2 | | 22=-8x+6 | | 38-2x=4(1+8x) | | 3x-2=3(x+2) |